Understanding Baṣara in the Context of Educational Psychology: The Impact of Symbol Interpretation - Annisa Mukti Ningrum; Achmad Khudori Soleh (Al-Qalam Institute, 2025)
This research is motivated by the importance of symbols in Islamic religious education, particularly the Baṣara symbol, which holds profound meaning in Islamic tradition but is rarely explored in educational psychology. This study aims to understand how the Baṣara symbol is applied in religious learning and its impact on students’ psychological development. Using a qualitative case study approach, data were collected through in-depth interviews, participant observation, and documentation, involving teachers and students as key informants. The findings indicate that the Baṣara symbol not only teaches moral values but also influences students’ emotional intelligence, enhancing empathy and emotional management. This research contributes to the understanding that Baṣara serves a dual function as a moral and psychological educational tool. Consequently, teaching methods need to be adapted to enable all students to understand this symbol more deeply, supporting their social and emotional development.